THE ROLE OF MENTAL HEALTH ON PHYSICAL EDUCATION TEACHERS’ JOB SATISFACTION - Vahid Bkhshalipour, (Sport Scientific And Practical Aspects, 2025)
General health is one of the most important components that has been considered in human society. It plays a significant role in health protection and promotion in human societies. Therefore, the purpose of this study was to investigate the role of mental health on physical education teachers’ job satisfaction. This study was a descriptive correlation research with an applied nature. The instrument was included the General Health Questionnaire (GHQ) and the Job Descriptive Index (JDI). The statistical population of this study was included all physical education teachers in Guilan province. The collected data was analyzed by the KS-test, the t-test, and Pearson’s correlation coefficient test. The results showed that 59.43% of gender indicators were men and 40.57% of them were women. 52.58% of subjects had an associate’s degree and a bachelor’s degree, 38.85% of them had a master’s degree, and 1.72% of them had a doctorate and were PhD students. Men’s total score of general health was 19.14 and women’s score was 14.34. Men’s total score of job satisfaction was 198.95 and women’s score was 184.66. The results also showed that the correlation coefficient between physical education Teachers’ mental health and job satisfaction was 0.114. This study showed that the components of mental health can predict employees’ job satisfaction level. It is suggested that the authorities have an appropriate program for employees’ sport and they lead the community to health by employees’persuasion to engage in sports activities.